The study of total sediment transport characteristics at Kanching forest waterfall / Siti Nur Khalila Zulkarnain, Sharifah Abdullah and Shahrul Jainudin - Zulkarnain, Siti Nur Khalila; Jainudin, Shahrul; Abdullah, Sharifah (2023)
Families and environment enthusiasts frequently visit Kanching Rainforest Waterfall, also known as Kanching Recreational Forest. It is located nearby in the Rawang neighbourhood to the north of Kuala Lumpur and has an area of around 47,000 square metres. Due to its proximity to the city, the region has become a popular place for people to enjoy picnics, camping, swimming, and jungle walks during the holidays. The movement or discharge of water flow is closely related with sediment. Since a specific discharge is necessary to propel and carry particles of a particular weight or size along the pathways. In essence, sediment estimates are so crucial because rivers in Malaysia continue to fill reservoirs with river water for daily use. Sedimentation in reservoirs can reduce the amount of accessible water, hence restricting its application. In this study, the Hjulström graph were used to predict the sediments and particles flow distributions, and the correlation between particle size and particle mobility in the flows of rivers was determined at three (3) checkpoints to examine the sediments and particles flow distributions. According to the data obtained, Checkpoint 1 has a particle velocity of around 0.4703 N/s, or 40 grammes per second, whereas Checkpoint 2 has a velocity of roughly 1.534 N/s, or 156 grammes per second. Lastly, Checkpoint 3 lacks a full load transfer. In addition to preserving one of the region's leisure areas, the significance of complete load transit estimation will ensure its maintenance. By using this method, the estimation of the total load that may be eroded along the river by calculating the total transport load can be forecasted hence, provide a maintenance program toward the rehabilitation of the Kanching Recreational Forest.